Clomipramine enhances prolactin and growth hormone responses to L-tryptophan. - Anderson, I; Cowen, P (1986)
The effects of the 5-hydroxytryptamine (5-HT) uptake inhibitor clomipramine on the prolactin (PRL) and growth hormone (GH) responses to L-tryptophan (LTP) were assessed in six normal subjects. Oral administration of 20 mg clomipramine 2 h prior to LTP infusion (50 mg/kg) significantly enhanced both endocrine responses, suggesting that the increases in plasma PRL and GH produced by LTP are mediated by 5-HT pathways. These findings, taken together with previous observations that 5-HT2 receptor antagonists do not attenuate the PRL response to LTP, suggest that the 5-HT-induced release of PRL in man may be mediated by 5-HT1 receptors.